The susceptibility of Lymnaea viatrix and Lymnaea columella to infection with Fasciola hepatica - Mattos, Mary Jane Tweedie de; Ueno, Hakaru (Pesquisa Agropecuaria Brasileira, 2014)
A comparison of the susceptibility between the two species of Lymnaea: L. columella and L. viatrix was performed using the same size of snail and the same degree of infection with miracidia of F. hepatica. It was confirmed that L. viatrix is an intermediate host of F. hepatica possessing higher susceptibility to the infection than L. columella, under laboratory conditions. Moreover it showed a high production rate of redia and metacercariae in L. viatrix. Development stages of F. hepatica in the two species of Lymnaea were also observed and the first appearance of sporocysts was observed six hours after the infection and first redia in the ninth day in both species; mature redia and cercariae in the twentieth day in L. viatrix, and in the twenty-seventh day in L. columella, respectively. Cercarial emergence in the twenty days in L. columella: metacercariae in the thirty-sixth day in both snail species. Presence of daughter redia of F.hepatica was observed on the twentieth day after experimental infection in L. calumella. The viability of metacercariae obtained was confirmed by oral infection to mice. Fasciola eggs wore delected in feces on the thirty-second day after infection. In necropsy, two adults of F.hepatica were colected.